Avaliação do emprego da filtração direta no tratamento de água com turbidez elevada por meio da pressedimentação: ensaios em escala de bancada - Felisberto Lucio (2013)
Drinking water must meet strict quality criteria, to not cause harm to the health of their consumers. However, the quantity and quality of water from surface water sources has been changing due to deterioration of watersheds, and two important indicators of problems associated with degradation of water quality are the peaks of turbidity and high concentration of Escherichia coli. The present study evaluates the use of pre-sedimentation without the application of chemicals to treat water with high turbidity, using direct filtration technique. The synthetic water used for the study was prepared by adding kaolin to tap water from drinking water distribution network of the Sanitation Company of Minas Gerais - COPASA. The results showed that pre-sedimentation improves the quality of raw water enabling the use of the direct filtration technique instead of complete cycle (conventional treatment). The turbidity removal efficiency employing pre-sedimentation was 63.8%, 77.8% and 93.9% for water Type I (50 NTU), II (100 UT) and III (500 UT), respectively. Two coagulants namely Aluminum sulfate and polyaluminum chloride were applied. The dosages applied to both coagulants were 2.5-35 mg/L for coagulation/flocculation/decantation, and 0-10 mg/L for presedimentation water followed by coagulation and direct filtration (PS-FD) on Whatman 40 filter paper. Basically, the PS-FD showed better results for the three study waters, especially in cases in which the coagulant applied was polyaluminum chloride, reducing turbidity to 0, 8 NTU, whereas for coagulation / flocculation / sedimentation turbidity values decreased to about 1.0 uT, where applied polyaluminium chloride. The polyaluminum chloride showed best results in terms of turbidity removing than aluminum sulfate, for the three types of water studied. In the chemical coagulation process, an additional dosage of coagulant beyond the necessary cause excess of electrolytes in the water, consequently the charge reversal phenomenon occurs, it was observed especially in the polyaluminium chloride coagulation diagrams because it is an inorganic polymer greater positively charged per mass relative to the aluminium sulfate